The impact of drug interactions and polypharmacy on antimicrobial therapy in the elderly. (January 2015) - Corsonello, A.; Abbatecola, A.M.; Fusco, S.; Luciani, F.; Marino, A.; Catalano, S.; Maggio, M.G.; Lattanzio, F.
Abstract: Infectious diseases are more prevalent in older people than in younger adults, and represent a major healthcare issue in older populations. Indeed, infections in the elderly are often associated with higher morbidity and mortality, and may present atypically. Additionally, older patients are generally treated with polypharmacy regimens, which increase the likelihood of drug–drug interactions when the prescription of an antimicrobial agent is needed. A progressive impairment in the functional reserve of multiple organs may affect either pharmacokinetics or pharmacodynamics during aging. Changes in body composition occurring with advancing age, reduced liver mass and perfusion, and reduced renal excretion may affect either pharmacokinetics or pharmacodynamics. These issues need to be taken into account when prescribing antimicrobial agents to older complex patients taking multiple drugs. Interventions aimed at improving the appropriateness and safety of antimicrobial prescriptions have been proposed. Educational interventions targeting physicians may improve antimicrobial prescriptions. Antimicrobial stewardship programmes have been found to reduce the length of hospital stay and improve safety in hospitalized patients, and their use in long-term care facilities is worth testing. Computerized prescription and decision support systems, as well as interventions aimed at improving antimicrobial agents dosage in relation to kidney function, may also help to reduce the burden of interactions and inherent costs.